2014
DOI: 10.1210/en.2013-1657
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctanesulfonate (PFOS) Perturbs Male Rat Sertoli Cell Blood-Testis Barrier Function by Affecting F-Actin Organization via p-FAK-Tyr407: An in Vitro Study

Abstract: Environmental toxicants such as perfluorooctanesulfonate (PFOS) have been implicated in male reproductive dysfunction, including reduced sperm count and semen quality, in humans. However, the underlying mechanism(s) remains unknown. Herein PFOS at 10-20 μM (∼5-10 μg/mL) was found to be more potent than bisphenol A (100 μM) in perturbing the blood-testis barrier (BTB) function by disrupting the Sertoli cell tight junction-permeability barrier without detectable cytotoxicity. We also delineated the underlying mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 59 publications
9
82
0
3
Order By: Relevance
“…In order to study transport of developing germ cells, one must first understand how cell junctions are regulated in the seminiferous epithelium. Studies using toxicant models, such as bisphenol A (BPA), cadmium, and perfluorooctanesulfonate (PFOS), have revealed that these environmental toxicants can target cell junctions in the testis to affect reproductive function [107109]. In addition to environmental toxicants, some male contraceptives under development also have been shown to target cell junctions in the testis.…”
Section: Mt Studies In the Rat Testismentioning
confidence: 99%
“…In order to study transport of developing germ cells, one must first understand how cell junctions are regulated in the seminiferous epithelium. Studies using toxicant models, such as bisphenol A (BPA), cadmium, and perfluorooctanesulfonate (PFOS), have revealed that these environmental toxicants can target cell junctions in the testis to affect reproductive function [107109]. In addition to environmental toxicants, some male contraceptives under development also have been shown to target cell junctions in the testis.…”
Section: Mt Studies In the Rat Testismentioning
confidence: 99%
“…There are few reports in the literature that assess the intratesticular level of toxicants following their acute exposure in adult rats. However, for in vitro studies in Sertoli cells, increasing concentrations, such as 0.1-10 μM for cadmium [11], 40-200 μM for BPA [25], and 5-20 μM for PFOS [14] were used in studies to monitor their effects on Sertoli cell TJ-barrier function. At these ranges, none of these toxicants were shown to be cytotoxic to Sertoli cells and a notable phenotype, such as a disruption of the TJ-barrier and changes in actin organization, was readily detectable, making them suitable for mechanistic studies.…”
Section: Dosing Issues Of Toxicants Used For Studiesmentioning
confidence: 99%
“…After isolation, Sertoli cells were plated on Matrigel (BD Biosciences, Billerica, MA)-coated coverslips, 12-well culture dishes, or Millicell HA (mixed cellulose esters) cell culture inserts (diameter, 12-mm; pore size, 0.45-m; effective surface area, 0.6-cm 2 ; EMD Millipore, Billerica, MA) at 0.05 (or 0.005 in experiments to visualize intercellular bridges, also known as TNT), 0.5, and 1.2 ϫ 10 6 cells/cm 2 , respectively. Cells at these densities were used for the following corresponding experiments: 1) dual-labeled immunofluorescence analysis, including F-actin staining; 2) lysate preparation for immunoblotting or RNA extraction for RT-PCR; and 3) assessment of the Sertoli cell TJ-permeability barrier function by quantifying transepithelial electrical resistance (TER) across the cell epithelium, as described (38,62). For immunofluorescence analysis, Sertoli cells plated on coverslips were then transferred to 12-well dishes with 2 ml/well F-12-DMEM for cell cultures.…”
Section: Methodsmentioning
confidence: 99%
“…For in vitro RNAi experiments in cultured Sertoli cells, Ն70 cells were randomly selected and examined in each experiment, including fascin 1 knockdown vs. controls of n ϭ 3 independent experiments (i.e., ϳ200 cells for each group). The intensity of fluorescence signals of a target protein such as fascin 1 in Sertoli cells in vitro or in the seminiferous epithelium of rat testes in vivo was quantified using ImageJ 1.45 (National Institutes of Health, Bethesda, MD; http://rsbweb.nih.gov/ij) in micrographs without the DAPI overlay to avoid interference, as described (61,62). For in vivo experiments, at least 50 randomly selected cross-sections of stage VII and VIII tubules were examined and analyzed with n ϭ 3 rats.…”
Section: VImentioning
confidence: 99%